PERANCANGAN PERTANIAN VERTIKAL YANG TERINTEGRASI UNTUK MENGATASI MASALAH PANGAN MASA DEPAN - Caroline Natalie; Martin Halim (Jurnal Sains, Teknologi, Urban, Perancangan, Arsitektur (Stupa), 2022)
Based on existing data, people in Indonesia will migrate to urban areas which will cause population problems. One of them is the food problem, coupled with the fast demand for fresh food in the capital, which lacks planting media and sunlight. Vertical agriculture is considered to be one solution to this problem. However, until now there has been no special building for vertical agriculture that stands in the capital. This is because to build a special building for vertical agriculture requires a large amount of cost and energy. The vertical design approach by rethinking the typology based on the analysis of existing studies produces a typology of open masses and blocks as edges, a typology of terracing and grid patterns, the placement of vertical farms in buildings using solar energy sources and technology (hybrids), and hydroponic, aquaponic, and hydroponic cultivation methods. and aeroponics with retail and office programs as supporting programs that are directly integrated with vertical farming as the main program. So that the "Integrated Vertical Farming" project is expected not only to be able to answer food and environmental problems, but also the economy. Keywords: Food Problems; Program; Typology; Vertical Farming AbstrakBerdasarkan data yang ada, masyarakat di Indonesia akan bermigrasi ke daerah perkotaan yang akan menimbulkan masalah kependudukan. Salah satunya adalah masalah pangan, ditambah dengan permintaan bahan pangan segar yang cepat di ibukota yang minim media tanam dan matahari. Pertanian vertikal dinilai menjadi salah satu solusi masalah tersebut. Namun hingga kini belum ada bangunan khusus pertanian vertikal yang berdiri di ibukota. Hal tersebut dikarenakan untuk membangun bangunan khusus pertanian vertikal membutuhkan biaya dan energi yang cukup besar. Pendekatan perancangan pertanian vertikal dengan rethinking typology berdasarkan analisis studi yang ada menghasilkan tipologi massa yang terbuka dan blok sebagai tepi, tipologi pola terasering dan grid, penempatan pertanian vertikal pada bangunan dengan penggunaan sumber energi matahari dan teknologi (hybrid), dan metode penanaman hidroponik, akuaponik, dan aeroponik dengan program retail dan office sebagai program pendukung yang terintegrasi langsung dengan pertanian vertikal sebagai program utama. Sehingga proyek “Integrated Vertical Farming” ini diharapkan tidak hanya mampu menjawab permasalahan pangan dan lingkungan, tetapi juga ekonomi.